PERENCANAAN EKONOMI DALAM PERSPEKTIF ISLAM - Imam, Muhammad Aniq (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2013)
AbstractEconomic planning, the process by which key economic decisions are made or influenced by central governments. It contrasts with the laissez-faire approach that, in its purest form, eschews any attempt to guide the economy, relying instead on market forces to determine the speed, direction, and nature of economic evolution. By the late 1960s the majority of the world’s countries conducted their economic affairs within the framework of a national economic plan. Economic planning refers to any directing or planning of economic activity outside the mechanisms of the  market.  Planning  is an  economic mechanism  for resource allocation and decision-making held in contrast with the market mechanism, where planning refers to a direct allocation of resources. Most economies are mixed economies, incorporating  elements of markets  and  planning  for distributing  inputs  and outputs. The level of centralization of decision-making in the planning process ultimately  depends  on  the  type  of planning  mechanism  employed; as such planning need not be centralized and may be based on either centralized or decentralized decision-making. Economic planning can apply to production, investment, distribution  or all three of these functions. Planning may take the form of directive planning or indicative planning. An economy primarily based on central planning is a planned economy; in a planned economy the allocation of resources is determined by a comprehensive plan of production which specifies output requirements. The Economic planning in Quranic perspective has faith and moral oriented as mentioned in Yusuf story in Holy Quran.Kata Kunci:  perencanaan ekonomi, ekonomi Islam, sistem Islam, Nabi Yusuf